Supplementation of sodium alginate-coated Clostridium butyricum after cottonseed protein concentrate replacement of fishmeal can improve growth, immunity, and intestinal health in Litopenaeus vannamei - Qi Wang; Depeng Fan; Yadong Hu; Hongyu Liu; Beiping Tan; Shiwei Xie; Qiang Chen (Aquaculture Reports)
The present study evaluated the effects of supplementation with sodium alginate-coated Clostridium butyricum (SACB) on growth, immune response, and intestinal health of Litopenaeus vannamei following the replacement of fishmeal with cottonseed protein concentrate (CPC). The freeze-drying method was used for bacterial agent preparation, with the optimal ratio of freeze-dried protectant being 15 % skimmed milk, 12 % β-cyclodextrin, 8 % glucose, and 0.5 % dipotassium hydrogen phosphate. Six isonitrogenous and isolipid diets were formulated, with one serving as the control group (CG, 25 % fishmeal content). The remaining five diets were formulated as fishmeal replacement groups (CPC replacing 40 % of fishmeal). The content of SACB (5.1 × 108 CFU/g) in the alternative groups were 0 % (SACB0), 0.06 % (SACB1), 0.24 % (SACB2), 0.96 % (SACB3) and 3.84 % (SACB4), respectively. The results showed that SACB improved the growth performance (P > 0.05). Malondialdehyde content was significantly inhibited in hepatopancreas after SACB addition (P < 0.01). In the SACB3 group, intestinal trypsin, amylase, and lipase activities were remarkably enhanced (P < 0.05). The alpha diversity index was significantly higher in the SACB3 group (P < 0.001). LEfSe analysis showed that the relative abundance of beneficial bacteria such as Lactobacillus_murinus, Lactobacillus_johnsonii_FI9785, and Ruminiclostridium_5 increased in the SACB3 group (P < 0.05). Propionic and butyric acid contents were significantly higher in the SACB3 group (P < 0.05). The relative expression of genes including phenoloxidase, relish, penaeidin-3a, and crustins was significantly upregulated in the SACB3 and SACB4 groups (P < 0.05). Contents of total essential amino acids, total non-essential amino acids, and total amino acids in muscles were significantly higher in SACB3 and SACB4 groups (P < 0.05). In summary, suitable SACB improved shrimp growth, immune response, intestinal short-chain fatty acids, and muscle amino acids. The optimum SACB addition of 1.96 % was determined through binary regression analysis of specific growth rate.